Furanocoumarin A: A Novel Anticancer Agent on Human Lung Cancer A549 Cells from Fructus liquidambaris - Fang, Hui; Ji, Hongmei (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background and Objective: The fruit of Fructus liquidambaris, which is recently being used for cancer treatment, has a history to be used as a traditional medicine in China for thousands of years. Materials and Methods: Ten kg of dried F. liquidambaris was obtained with 70% alcohol-water solution under reflux for three times. The condensed extract was obtained from petroleum ether, ethyl acetate and N-butyl alcohol, respectively. Ethyl acetate extract was subjected to silica gel column, Sephadex LH-20, ODS column chromatography and RP-HPLC column chromatography to yield a new compound (1). The structure was identified through intensive analysis of NMR and MS spectra. The antitumor mechanism of the furanocoumarin A on human lung cancer A549 cells was confirmed by detecting the apoptosis-related proteins. Results: Furanocoumarin A (1), a novel furanocoumarin constituent was isolated and identified from F. Liquidambaris. The IC50 value of furanocoumarin A on A549 cell lines was 65.28±5.36μM obtained by the method of MTT. The compound could induce the apoptosis of A549 cells by inducing 21.5% early apoptosis and 32.4% late apoptosis at the concentration of 60μmol/L. Western blot analysis indicated that protein expressions of p53, caspase 3 and Bax increased in a dose-dependent manner between the concentrations from 40 to 80μM. The protein expression of Bcl-2 decreased the concentration of 60 and 80μM. The ratio of Bcl-2 to Bax was inversely proportional to the dose concentration. Conclusion: Furanocoumarin A could be a novel anticancer agent from herbal medicine.
Keywords: furanocoumarin